Research on the Relationship Between Visual Perception in Psychology and Photographic Creation (Journal of humanities and social sciences exploratio, 2025)
Photography, as a visual art, is closely linked to the complex processes of human inner activities. This paper explores how psychological principles subtly influence photography creation and photo appreciation. In photographic images, Gestalt theory, visual perception mechanisms and neuroaesthetics play crucial roles. It analyzes the effect of the basic laws of visual perception on photographic composition and aesthetic expression, revealing the in-depth dialogue between creative behaviors and internal psychological responses. Mastering the psychological mechanisms of visual perception can not only enhance the artistic appeal and communication effect of photographic works, but also enable people to perceive and understand the world from a clearer perspective. This lays a psychological foundation for the theoretical breakthrough and practical innovation of photography. Gestalt principles of perceptual organization, such as the principle of figure-ground, provide a scientific basis for photographic composition; the principles of closure and simplification improve cognitive efficiency and enhance aesthetic feelings; the principle of similarity enriches the sense of complexity and stimulates the audience's interest in exploration. Visual perception itself is regarded as the interaction result of bottom-up sensory information processing and top-down cognitive framework application, which is deeply marked by the respective psychological maps of creators and viewers. Neuroaesthetics further uncovers the secret that excellent photographic works achieve a balance between predictive error and cognitive reward at the neural level. The research finds that photographic creation is itself a powerful psychological construction activity. Through visual storytelling, it helps individuals organize fragmented experiences, express hidden emotions and construct a network of meanings for their self-world. From the perspective of academic theory and practical application, this paper outlines a photography creation framework based on the principles of visual cognition, providing a unique methodological guidance from the psychological perspective for photography education, creation and criticism.
Keywords: Art aesthetics; Photographic psychology; Photographic theory; Vision and Narration; Gestalt principles; Future technology